Smoking among nurses of the national hospital in Lima, Peru (Revista Latino-Americana de Enfermagem, 2010)
Nurses have unique opportunities to help their patients to stop smoking. The aim of this study was to identify, among nurses of a hospital, the consumption of smoking products, their attitudes and information received on smoking. It was a descriptive study, carried out with 204 (48%) nurses of the Hospital Arzobispo Loayza, Lima, Peru. The Global Health Professional Survey (GHPS) was used. Among the sample the prevalence of smoking in life was 67.1% and 3% in the last month. The majority of nurses presented positive attitudes and knew the importance and responsibility of advising patients to quit. The majority had received general information regarding the topic, though half of them had not received specific information regarding treatment. In view of the importance of this theme, this study identified a need for further research of this nature as well as revision of the curricula regarding the approach toward the theme of smoking.